18F-FDG PET/CT revealed sporadic schwannomatosis involving the lumbar spinal canal and both lower limbs: a case report - Li, Xiaotian; Hu, Xianwen; Wang, Pan; Cai, Jiong (Frontiers in Medicine, 2024)
Schwannomatosis is a rare autosomal dominant hereditary syndrome disease characterized by multiple schwannomas throughout the body, without bilateral vestibular schwannoma or dermal schwannoma. The most common location of schwannomatosis is the head and neck, as well as the limbs, while multiple schwannomas in the lumbosacral canal and lower extremities are relatively rare. Here we report a 79-year-old female patient diagnosed with schwannomatosis, MRI and contrast-enhanced imaging revealed multiple schwannomas in both lower extremities, 18 F-FDG PET/CT examination revealed that in addition to multiple tumors with increased 18 F-FDG uptake in both lower extremities, there was also an increased 18 F-FDG uptake in a mass in the lumbosacral canal. These masses were confirmed to be schwannomas by pathology after surgery or biopsy. 18 F-FDG PET/CT findings of schwannomas were correlated with MRI and pathological components. Antoni A area rich in tumor cells showed significant enhancement on contrast-enhanced T1WI, and PET/CT showed increased uptake of 18 F-FDG in the corresponding area, while Antoni B region rich in mucus showed low enhancement on contrast-enhanced T1WI, accompanied by a mildly increased 18 F-FDG uptake.